Rates of Anterior Cruciate Ligament Rerupture in Adolescent Patients with and without Patella Alta - Rider, Danielle; Gowd, Anirudh K.; Torres, LeeAnne F.; Kaplin, Lisa W.; Waterman, Brian R. (The Journal of Knee Surgery, 2022)
The objective of this study was to compare rates of anterior cruciate ligament (ACL) failure among adolescent patients to evaluate patella alta as a high-risk variable. Demographic and surgical data were retrospectively queried for patients ≤18 years of age with primary ACL reconstruction performed at a single academic center between 2011 and 2016 and minimum of 2-year clinical surveillance. Patellar height indices, including Caton–Deschamps index (CDI) and Insall–Salvati index (ISI), were retrospectively calculated from preoperative imaging to assess the presence of patella alta. Failure was defined as (1) ACL graft rerupture, (2) Lachman's grade 2 + , (3) presence of pivot shift, and (4) side-to-side difference of 3 mm on KT-1000 arthrometer. A total of 184 patients (84 females and 100 males) and 192 knees were identified, with an average age of 16.2 ± 1.8 years. Of these, 30 (15.63%) experienced ACL failure. Male sex was the only significant risk factor for rerupture (p = 0.026). The mean CDI was 1.06 ± 0.17 and mean ISI was 1.04 ± 0.15. Of the 49 knees that met criteria for patella alta on radiographic evaluation, rerupture occurred in seven (14.29%). Patella alta was not a significant risk factor for ACL failure among adolescent patients (p = 0.359 and 0.277). Only male sex was associated with increased rates of ACL failure. Age, graft selection technique, fixation construct, and presence of patella alta were not risk factors for reinjury. This study is a therapeutic case series and reflects level of evidence IV.
Keywords: anterior cruciate ligament; patella alta; Caton–Deschamps index; Insall–Salvati index; rerupture